Autogenous tooth transplantation for replacing a lost tooth: case reports - Kang, Ji-Youn; Chang, Hoon-Sang; Hwang, Yun-Chan; Hwang, In-Nam; Oh, Won-Mann; Lee, Bin-Na (Restorative dentistry & endodontics, 2013)
The autogenous tooth transplantation is an alternative treatment replacing a missing tooth when a suitable donor tooth is available. It is also a successful treatment option to save significant amount of time and cost comparing implants or conventional prosthetics. These cases, which required single tooth extraction due to deep caries and severe periodontal disease, could have good results by transplanting non-functional but sound donor tooth to the extraction site.